PENDAMPINGAN MODIFIKASI GAYA HIDUP (POLA MAKAN & AKTIVITAS FISIK) UNTUK MENURUNKAN KADAR GULA DARAH PADA PASIEN PRADIABETES - Basir, Ita Sulistiani; Fatimah M. Arsad, Siti (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2025)
Diabetes is a chronic disease that occurs when the pancreas does not produce enough insulin or when the body cannot use the insulin it produces effectively. Insulin is a hormone that regulates blood glucose. Hyperglycemia, also called high blood glucose or high blood sugar, is a common effect of uncontrolled diabetes and over time causes serious damage to many body systems, especially the nerves and blood vessels. The development of diabetes mellitus is usually preceded by Prediabetes, which is characterized by impaired fasting glucose. Research has shown that prediabetes is a toxic state that leads to cardiovascular disease associated with diabetes. Preventing type 2 diabetes involves a healthy lifestyle: a balanced diet, regular exercise, and avoiding sugary and processed foods. Maintaining a healthy weight is essential because obesity increases the risk. Even small weight losses can significantly reduce the risk of type 2 diabetes. Community service activities by modifying patient lifestyles have an impact on the blood sugar results of prediabetes community patients in Ombulo Village.